Public Financial Management Reforms: The Role of Ipsas in Latin‐America. (February 2016) - Brusca, Isabel; Gómez‐villegas, Mauricio; Montesinos, Vicente
Summary: During the last 30 years, many public administration reforms promoted by New Public Management have been undertaken. These reforms have spread to Latin‐American countries and include changes in governmental accounting systems, where the implementation of International Public Sector Accounting Standards (IPSASs) has been a stimulus for modernization. This article aims to clarify the situation of IPSASs implementation in the Latin‐American context as well as the stimuli for and effects of their implementation. The analysis shows that there is an emerging international trend to adopt IPSASs in Latin‐American countries although at the same time, there are evident obstacles to achieving reform goals. In Colombia, reforms are still underway, and the usefulness of IPSASs to improve decision‐making at an organisational level cannot be evaluated. Meanwhile, in Peru, the modernization is more rhetorical than real, and many efforts remain to be made for the effective implementation. Copyright © 2016 John Wiley & Sons, Ltd.